Expectations and learning in Iowa - Bondarenko, Oleg; Bossaerts, Peter (Journal of Banking & Finance, 2000)
We study the rationality of learning and the biases in expectations in the Iowa Experimental Markets. Using novel tests developed in (Bossaerts, P., 1996. Martingale restrictions on equilibrium security prices under rational expectations and consistent beliefs. Caltech working paper; Bossaerts, P., 1997. The dynamics of equity prices in fallible markets. Caltech working paper), learning in the Iowa winner-take-all markets is found to be in accordance with the rules of conditional probability (Bayes' law). Hence, participants correctly update their beliefs using the available information. There is evidence, however, that beliefs do not satisfy the restrictions of rational expectations that they reflect the factual distribution of outcomes.